On properties of fuzzy ideals in po-semigroup - Samit, Kumar Majumder; Sujit, Kumar Sardar (Armenian Journal of Mathematics, 2009)
In this paper some properties of fuzzy ideals and fuzzy ideal extensions in a po-semigroup have been investigated.